Plasma N terminal pro-brain natriuretic peptide and cardiotrophin 1 are raised in unstable angina. Issue 4 (1st October 2000) - Talwar, S; Squire, I B; Downie, P F; Davies, J E; Ng, L L
Abstract : OBJECTIVE: To compare circulating concentrations of N terminal pro-brain natriuretic peptide (N-BNP) and cardiotrophin 1 in stable and unstable angina. DESIGN AND SETTING: Observational study in a teaching hospital. PATIENTS: 15 patients with unstable angina, 10 patients with stable angina, and 15 controls. MAIN OUTCOME MEASURES: Resting plasma N-BNP and cardiotrophin 1 concentrations. RESULTS: N-BNP concentration (median (range)) was 714 fmol/ml (177–3217 fmol/ml) in unstable angina, 169.5 fmol/ml (105.7–399.5 fmol/ml) in stable angina (p = 0.005 v unstable angina), and 150.5 fmol/ml (104.7–236.9 fmol/ml) in controls (p < 0.0001 v unstable angina; NS v stable angina). Cardiotrophin 1 concentration was 142.5 fmol/ml (42.2–527.4 fmol/ml) in unstable angina, 73.2 fmol/ml (41.5–102.1 fmol/ml) in stable angina (p < 0.05 v unstable angina), and 27 fmol/ml (6.9–54.1 fmol/ml) in controls (p < 0.0005 v stable angina; p < 0.0001 v unstable angina). Log cardiotrophin 1 correlated with log N-BNP in unstable angina ( r  = 0.93, p < 0.0001). CONCLUSIONS: Both circulating N-BNP and cardiotrophin 1 are raised in unstable angina, while cardiotrophin 1 alone is raised in stable angina. The role of cardiotrophin 1 and the relation between cardiotrophin 1 and N-BNP in myocardial ischaemia remain to be defined.